Transparency in state debt disclosure - Bo Zhao; Wen Wang (Federal Reserve Bank of Boston, 2017)
We develop a new measure of relative debt transparency by comparing the amount of state debt reported in the annual Census survey and the amount reported in the statistical section of the state Comprehensive Annual Financial Report (CAFR). GASB 44 requires states to start reporting their total debt in the CAFR statistical section in FY 2006. However, states are allowed to use accounting choices to exclude some dependent agencies' debt, which contributes to a gap between the two data sources. The regression results suggest that the gap tends to increase when states face greater fiscal stress or less political competition. Such patterns are not found in the pre-GASB 44 period.
Keywords: H74; H83; 330; fiscal transparency; state debt; GASB; accounting choices; dependent agencies